Virginia's Blues, Country, and Gospel Records, 1902-1943 : An Annotated Discography - Lornell, Kip, 1953- (Book collections on Project MUSE., 1989)
During the years before World War II, hundreds of traditional musicians were sought out by commercial record companies, brought to New York or into local -- often makeshift -- studios, to cut recordings that would be marketed as ""race"" and ""hillbilly"" music. Virginia was home to scores of these performers, several of whom were to become internationally known. Among them were the Carter Family, the Golden Gate Quartet, Charlie Poole, and the Stoneman Family, whose music has touched millions of listeners far beyond the confines of the Old Dominion. It is this historically important body of re.